1979
DOI: 10.1042/bj1810245
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the heparin-releasable lipase in situ in the rat liver

Abstract: Immunofluorescence and immuno-electron microscopy were used for the localization of the heparin-releasable lipase in situ in the rat liver. The lipase is located exclusively on the liver endothelial cells. No labelling could be detected on the parenchymal of Kupffer cells, or in the livers of heparin-pretreated animals. The physiological significance of the endothelial localization of the hepatic lipase is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
1

Year Published

1980
1980
2005
2005

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(46 citation statements)
references
References 15 publications
(16 reference statements)
1
44
1
Order By: Relevance
“…Tissue fractionation studies have shown that the heparin-releasable enzyme is associated with the plasma membrane fraction of rat liver homogenates [6,14]. In rat [15,16] and chicken [17] liver, the enzyme is synthesized and secreted by the parenchymal cells and subsequently bound to high-affinity binding sites on the non-parenchymal (endothelial) cells [18,19]. Recent experiments have shown that there is only one alkaline lipase in rat liver [ 201.…”
Section: Liver Triacylglycerol Lipasesmentioning
confidence: 99%
“…Tissue fractionation studies have shown that the heparin-releasable enzyme is associated with the plasma membrane fraction of rat liver homogenates [6,14]. In rat [15,16] and chicken [17] liver, the enzyme is synthesized and secreted by the parenchymal cells and subsequently bound to high-affinity binding sites on the non-parenchymal (endothelial) cells [18,19]. Recent experiments have shown that there is only one alkaline lipase in rat liver [ 201.…”
Section: Liver Triacylglycerol Lipasesmentioning
confidence: 99%
“…Hepatic lipase is present in the liver and is believed to play a role in the metabolism of highdensity lipoproteins, intermediate-density lipoproteins and chylo-micron remnants [5][6][7][8][9]. Both lipoprotein lipase and hepatic lipase are synthesized and secreted by parenchymal cells and are bound specifically to the endothelial-cell lining [10][11][12][13][14][15]. It is generally assumed that both hepatic lipase and lipoprotein lipase are bound to heparan sulphates at the endothelium [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Human HL is a 476 -amino-acid glycoprotein that is synthesized by hepatocytes and binds to external surfaces of hepatic cells. 3,4 Studies in animal models and HL-deficient humans [5][6][7][8] suggested that HL is involved in the conversion of IDLs to LDLs, and in the catabolism of large lipid-rich HDLs (reviewed in Reference 1). HL also enhances the direct binding and uptake of cholesteryl ester-rich VLDL and chylomicron remnants by hepatocytes.…”
mentioning
confidence: 99%